2010
DOI: 10.1007/s00418-010-0702-1
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin is depleted from proximal tubules in experimental and human acute kidney injury

Abstract: Ischemia remains the most common cause of acute kidney injury (AKI). Decreased intercellular adhesion and alterations in adhesion molecules may contribute to the loss of renal function observed in AKI. In the present study, we evaluated the distribution of adhesion molecules in the human kidney and analyzed their expression in human and experimental AKI. Specimens of human kidneys obtained from patients with and without AKI were stained for the cell adhesion molecules E-cadherin, N-cadherin and beta-catenin. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…This may be explained by the fact that L1CAM is a membrane glycoprotein normally expressed at the basolateral membrane of the collecting-duct epithelial cell, which with injury is translocated to the apical membrane (23,24). We studied other potentially important biomarkers, including AQP2, a water channel (25); E-cadherin, a cell adhesion molecule (8,9,26,27); and N-cadherin, another member of the cadherin family (9,28,29). Although the excretion of these candidate proteins was altered in our casepatients, they did not correlate with renal function or with a reduced GFR.…”
Section: Discussionmentioning
confidence: 83%
“…This may be explained by the fact that L1CAM is a membrane glycoprotein normally expressed at the basolateral membrane of the collecting-duct epithelial cell, which with injury is translocated to the apical membrane (23,24). We studied other potentially important biomarkers, including AQP2, a water channel (25); E-cadherin, a cell adhesion molecule (8,9,26,27); and N-cadherin, another member of the cadherin family (9,28,29). Although the excretion of these candidate proteins was altered in our casepatients, they did not correlate with renal function or with a reduced GFR.…”
Section: Discussionmentioning
confidence: 83%
“…AKI induced by ischaemia or toxins was characterised by the impairment of kidney function due to the loss of tubular epithelial polarity 31 . Tissue integrity was checked by the immunohistochemical detection of the adhesion junction molecules E- and N-cadherin.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, AKI induced by ischaemia or calcineurin inhibitors depleted the expression of N-cadherin while E-cadherin was unaffected 31 . Our study corroborated these findings and demonstrated that the depletion of N-cadherin was attenuated by pBM-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] As shown in Supplemental Figure 2, many tubules were labeled by FITC-PNA from cortex through medulla, but only tubules in the cortex were costained with EGFR. Because the majority of renal tubules in the cortex are proximal tubules, this finding suggests that EGFR is predominantly expressed in proximal tubular cells.…”
Section: Egfr Phosphorylation Andmentioning
confidence: 91%